Quantification of patellar tendon reflex by motion analysis - Tham, L.K. (2011)
This study collected quantitative measurements of the patellar tendon reflex using 3-dimensional motion analysis. The study was conducted in the Motion Analysis Laboratory, Faculty of Engineering, University of Malaya, Kuala Lumpur, Malaysia. Patellar tendon reflex of a group of healthy subjects involving 28 males and 22 females was examined. The left and right patellar tendons were tapped by a Queen Square reflex hammer with three different angles where the reflex hammer was released. The phenomenon of Jendrassik maneuver was tested by tapping on the tendon with the hammer raised to an angle of 60Â°. The purpose of this was to investigate the effect of reinforcement method on reflex responses. Results of the study showed that the patellar tendon reflex response of male subjects were higher at higher tapping force. Reflex response of the left and the right side did not show any significant difference. The study of tapping force on reflex response showed greater response at increasing tapping force. The reinforcement method named Jendrassik maneuver increased patellar tendon reflex response for both legs.